Blood pressure screening during the May Measurement Month 2017 programme in Vietnam—South-East Asia and Australasia - Van Minh, Huynh (Eur Heart J Suppl, 2019)
Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative aimed at raising awareness of high BP and to act as a temporary solution to the lack of screening programmes worldwide. Our aim was to screen for hypertension (HTN) and cardiovascular risk factors in people aged ≥18 years in the community, thereby define the proportion of subjects with elevated BP and assess the awareness and the effectiveness of its treatment. An opportunistic cross-sectional survey of volunteers aged ≥18 years was carried out in May 2017. Blood pressure measurement, the definition of HTN and statistical analysis followed the standard MMM protocol. From May 2017 to June 2017, through 10 cities/provinces in Vietnam, 10 993 individuals with mean age 49.1 ± 16.2 years were screened during MMM17. After multiple imputation, 3154 (28.7%) had HTN. Of individuals not receiving antihypertensive medication, 1509 (16.1%) were hypertensive. Of individuals receiving antihypertensive medication, 620 (37.7%) had uncontrolled BP. Raised BP was also associated with additional risk factors including smoking, alcohol, overweight-obesity, and diabetes. May Measurement Month 17 was the largest BP screening campaign ever undertaken in Vietnam. Undiagnosed and uncontrolled HTN in Vietnam remains a substantial health problem. Local campaigns applying standardized methods such as MMM17, will be highly useful to screen for the significant number of individuals with raised BP and increase the awareness of HTN.